2021
DOI: 10.1111/vox.13090
|View full text |Cite
|
Sign up to set email alerts
|

Exchange transfusions in severe Rh‐mediated alloimmune haemolytic disease of the foetus and newborn: a 20‐year overview on the incidence, associated risks and outcome

Abstract: Background and objectives Guidelines and indications for exchange transfusion in haemolytic disease of the foetus and newborn (HDFN) have changed drastically in the past decades, causing a decline in exchange transfusion rate. This study aims to evaluate the incidence of exchange transfusions (ETs) in neonates with Rh‐mediated HDFN over the past 20 years at our centre, and report potentially ET‐related complications as well as indicators for bilirubin encephalopathy. Material and methods In this observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(50 reference statements)
2
10
1
Order By: Relevance
“…5 Bloodstream infections such as CLABSI, are a major cause of morbidity and mortality in neonatal intensive care units (NICU) worldwide, leading to prolonged hospital stays and increased health-care expenditures. 6 Despite the numerous outcomes studied among neonates with HDFN including hematological and cardiorespiratory complications, long-term neurodevelopmental outcome, and mortality, 5,[7][8][9][10][11] the incidence of cultureproven early-onset (EOS) and late-onset (LOS) sepsis, including CLABSI, is not well described. Moreover, in the context of an existing inherently low risk of infection, equivocal evidence regarding potential risk factors for sepsis evaluation and clinical indication for antibiotic therapy remains absent.…”
Section: Introductionmentioning
confidence: 99%
“…5 Bloodstream infections such as CLABSI, are a major cause of morbidity and mortality in neonatal intensive care units (NICU) worldwide, leading to prolonged hospital stays and increased health-care expenditures. 6 Despite the numerous outcomes studied among neonates with HDFN including hematological and cardiorespiratory complications, long-term neurodevelopmental outcome, and mortality, 5,[7][8][9][10][11] the incidence of cultureproven early-onset (EOS) and late-onset (LOS) sepsis, including CLABSI, is not well described. Moreover, in the context of an existing inherently low risk of infection, equivocal evidence regarding potential risk factors for sepsis evaluation and clinical indication for antibiotic therapy remains absent.…”
Section: Introductionmentioning
confidence: 99%
“…in the 20-year experience (2000-2020) of ET in infants with gestational age equal to or greater than 35 weeks with HDN by Rh at the Leiden University Medical Center. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Inherent to invasive nature of the procedure and the use of central lines, exchange transfusions are not without risk. Although in experienced hands the mortality rate of exchange transfusions may be as low as 0-0.3% in (near-) term neonates with increasing rates at a lower gestational age, complications associated with exchange transfusions should be considered [80][81][82][83]. Frequently occurring complications are thrombocytopenia < 100•10 9 /L (31≥90%) [81,84], hypocalcemia (1-47%) [81,82,84], leukocytopenia < 5•10 9 /L (33%) and sepsis related to the procedure (10%) [81].…”
Section: Early Phase: Hyperbilirubinemiamentioning
confidence: 99%
“…Although in experienced hands the mortality rate of exchange transfusions may be as low as 0-0.3% in (near-) term neonates with increasing rates at a lower gestational age, complications associated with exchange transfusions should be considered [80][81][82][83]. Frequently occurring complications are thrombocytopenia < 100•10 9 /L (31≥90%) [81,84], hypocalcemia (1-47%) [81,82,84], leukocytopenia < 5•10 9 /L (33%) and sepsis related to the procedure (10%) [81]. In a study by Jansen et al, it was found that neonates with HDFN with a central line had a higher risk for lateonset sepsis (RR 1.11, 95% CI: 1.04-1.20).…”
Section: Early Phase: Hyperbilirubinemiamentioning
confidence: 99%